MEASURE OFF TERMITES DIVERSITY AND ABUNDANCE IN VARIOUS OILPALM TYPOLOGY IN TULANG BAWANG DISTRICT, LAMPUNG PROVINCE - Lismaini, Lismaini (Operations Research: International Conference Series, 2022)
The study was conducted in oilpalm land in Tiuh Tohou Village, Menggala, Tulang Bawang District of Lampung Province.  This research aimed to measure off diversity and abundance in various oilpalm typologies in Tulang Bawang District, to study the relative abundanceof termites was highest in various oilpalm typology in Tulang Bawang and to find out the influence of environmental factors on termites diversity . The termites were sampled using the transect method.  Data were analyzed using ANOVA and LSD test at 5% level of significance.  Six termites genera were found acroos five typologies of oilpalm (old oilpalm, young oil palm, shrub/grass, cassava and swamp land), i.e. Globitermes, Odontetermes, Macrotermes, Hypotermes, Schedorhinotermes and Bulbitermes.  However, it was estimated that three more other genera would be found if the number of samples (typology) was increase (extrapolated).  There were differences in the diversity of termites accros oilpalm typologies (five genera in old oilpalam, four genera in young oilpalm, two genera in cassava, and only one genus in shrub/grass.  The relative abundanceof termites was highest in the old oilpalm (18 counts), followed by young oilpalm (14 counts), cassava (5 counts) and shrub/grass (3 counts).  The ranking of termites relative abundance had an exponential pattern, with Macrotermes and Bulbitermes being the most and the least abundance genera, respectively. Environmental factor that effect the richness of the termite genus are humidity, wood volume and litter weightand environmental factor that effect distribution and frequency of termite findings are influenced by frequency of termite findings are influenced by the level of canopy cover, humidity, wood volume, litter weight and litter organic C.